MONODRAM WE WSPÓŁCZESNEJ DRAMATURGII ROSYJSKIEJ - Piłat, Walenty (Acta Neophilologica, 2018)
The aim of the article is to analyze selected plays of Yevgeny Grishkovets, Lyudmila Petrushevska, Nikolaj Kolada, and other contemporary Russian playwrights, attending to their mode, that is a monodrama. The essence of a monodrama is its intended monologicquality, however, each monologue presupposes a dialog with the potential recipient. It is emphasized in the article that even though it is a short piece of dramatic writing, a monodrama often emerges as a source of knowledge about a modern man and his relations with the reality that surrounds him. It is the conviction of the author of the article that the analyzed plays serve as excellent illustrations of this thesis.